The past, present, and future all matter: how time perspective is associated with optimism and sensation seeking among young adults - Konowalczyk, Svenja; Buhl, Monika; Moon, Julia; Mello, Zena R. (Research in human development, 2019)
We used a multidimensional model of time perspective to examine how feelings and thoughts about the past, present, and future were related to optimism and sensation seeking among young adults. The dimensions of time perspective assessed were time feelings, the positive and negative emotions one has about the past, present, and future; time frequency, the amount of thinking about each time period; and time orientation, the relative emphases toward the time periods. Optimism and sensation seeking were self-reported and participants included 463 young adults. Variable-based analyses indicated that reporting more positive and less negative feelings about the time periods or emphasizing the present and future simultaneously were associated with greater optimism. For sensation seeking, boredom susceptibility was especially associated with the time perspective dimensions. Person-centered analyses based on time feelings and time frequency yielded four profiles (i.e., Mindful, Discontent, Bleak, and Indifferent) that were associated with both optimism and sensation seeking.
Gesehen am 21.01.2020